Three Filipino women - Jose, Francisco Sionil 1924- (Random House, 1992)
These novellas by the foremost writer of the Philippines are portraits of three women who, somewhat like the archipelago itself, are troubled, victimized, and beautiful. Here is the swirling cultural life and physical world of the twentieth-century Philippines, with its gulf between immense wealth and crushing poverty, humane social concerns and self-interest, political radicalism and police-state repression.